3D фреймові моделі комутаційних елементів Березовського програмно конфігурованих комутаційних структур - Berezovsky, S. A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2018)
The frame 2D and 3D models of patented by Berezovsky switching ele-ments are proposed in relation to the construction of topologies of switching structures admissible for reconfiguration. It has been revealed that the use of frame models by Berezovsky switching elements allows to visualize the information about the state of the structure of switching elements, to vary the number of independent inputs and outputs, and provides additional possibilities in the simulation of topologies of modern structures with separated by planes data and control. The method of formation of states of the switching structure topology elements has been proposed.